Corrosion in reinforced concrete structures - Böhni, Hans, 1937- (Woodhead ; CRC Press, 2005)
Reinforced concrete has the potential to be very durable and capable of withstanding a variety of adverse environmental conditions. However, failures in the structures do still occur as a result of premature reinforcement corrosion. In this authoritative book the fundamental aspects of this complex process are analysed; focusing on corrosion of the reinforcing steel, and looking particularly, at new scientific and technological developments. Monitoring techniques, including the newly developed online-monitoring, are examined, as well as the numerical methods used to simulate corrosion and perform parameter studies. The influence of composition and microstructure of concrete on corrosion behaviour is explored. The second half of the book, which deals with corrosion prevention methods, starts with a discussion on stainless steels as reinforcement materials. There are comprehensive reviews of the use of surface treatments and coatings, of the application of corrosion inhibitors and of the application of electrochemical techniques. In each case the necessary scientific fundamentals are explained and practical instances of use are looked at. This is an invaluable guide for engineers, materials scientists and researchers in the field of structural concrete. Fundamental aspects of corrosion in concrete are analysed in detailExplores how to minimise the effects of corrosion in concreteInvaluable guide for engineers, materials scientists and researchers in the field of structural concrete.